2002
DOI: 10.1016/s0006-3495(02)75405-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Difference in Heat Capacity Increments for Ca2+ Binding to Two α-Lactalbumins

Abstract: Thermodynamic parameters for the unfolding of as well as for the binding of Ca(2+) to goat alpha-lactalbumin (GLA) and bovine alpha-lactalbumin (BLA) are deduced from isothermal titration calorimetry in a buffer containing 10 mM Tris-HCl, pH 7.5 near 25 degrees C. Among the different parameters available, the heat capacity increments (Delta C(p)) offer the most direct information for the associated conformational changes of the protein variants. The Delta C(p) values for the transition from the native to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Under identical conditions T m ,DSC and Δ H unf of BLA is 68.7°C and 318 kJ · mol −1 , respectively 43–45. In previous work we already observed that at 25°C the Δ H values for the unfolding of Ca 2+ ‐bound GLA are larger than those of BLA: 216 kJ · mol −1 and 196 kJ · mol −1 , respectively 46. Visibly, the higher enthalpy of unfolding of GLA compared to that of BLA is a stabilizing factor over the whole temperature range.…”
Section: Resultsmentioning
confidence: 81%
“…Under identical conditions T m ,DSC and Δ H unf of BLA is 68.7°C and 318 kJ · mol −1 , respectively 43–45. In previous work we already observed that at 25°C the Δ H values for the unfolding of Ca 2+ ‐bound GLA are larger than those of BLA: 216 kJ · mol −1 and 196 kJ · mol −1 , respectively 46. Visibly, the higher enthalpy of unfolding of GLA compared to that of BLA is a stabilizing factor over the whole temperature range.…”
Section: Resultsmentioning
confidence: 81%
“… a Vanhooren et al 2002; b Hendrix et al 2000; c Anderson et al 1997; d Aramini et al 1992; e Kronman et al 1981; f Bratcher and Kronman 1984; g Segawa and Sugai 1983; h Gerken and Dearborn 1984; i Permyakov et al 1981; j Schaer et al 1985. …”
Section: Ca2+ Association Constants (Ka) For α‐Lactalbumin or Hamletmentioning
confidence: 99%
“…Second, we monitored the ANS binding to the decalcified apo‐BLA with ITC at two representative temperatures: 20 and 40 °C. This is to see if there are any differences in the binding mechanism with respect to temperature, because the formation of authentic MG was reported to depend heavily on temperature (Vanhooren et al ., ) and accelerated at an elevated temperature such as 40 °C (Veprintsev et al ., ). We expect that the thermodynamic data on ANS and apo‐BLA interaction obtained from this study would serve as a useful reference for investigating the binding of other hydrophobic ligands such as oleic acid to apo‐BLA (Lin et al ., ).…”
Section: Introductionmentioning
confidence: 97%